The relevance of Asteraceae family plants in most of the neuropsychiatric disorders treatment - SAMSON GUENNE; IOANA-MIRUNA BALMUS; ADAMA HILOU; NABERE OUATTARA; MARTIN Kiendrebéogo; ALIN CIOBICA; RADU LEFTER; VLADIMIR POROCH; Daniel Timofte (International Journal of Phytomedicine, 2016)
Many of the traditional medicinal plants belong to one of the largest plant families: the Asteraceae family. These plants are widely used in alternative medicine due to their effects on the nervous system, being studied both on cellular and animal models. In this way, medicinal plants are preferred in drug therapy research due to the wide population interest. The Asteraceae plants phytochemical composition is mainly consisted in cholinergic, dopaminergic or serotonergic molecules which are involved in the pathophysiology of the neuropsychiatric disorders such as Alzheimer’s disease, Parkinson’s disease, schizophrenia, autism, anxiety or depression. Therefore, this review aims to comprise all the available information regarding the neurological activity of Asteraceae family plants in order to find further correlations between different components in order to explain their neuropsychiatric potential use.